The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.3767/000651913x671281
|View full text |Cite
|
Sign up to set email alerts
|

Mapania sapuaniana (Cyperaceae), a new sedge species from Sarawak

Abstract: Mapania sapuaniana, a spectacular new sedge species from Lanjak Entimau, Sarawak, is described and illustrated. It is closely related to M. richardsii and M. borneensis but differs in having broad leaves with a distinct pseudopetiole, reddish purple or maroon coloration on the underside of the leaf and petiole and an inflorescence composed of several spikes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…During the course of 130 days post-transplanting, M. cuspidata developed an average of 7.7 new leaves with leaf production rate of 15.8 days/leaf. The findings of this study are substantial yet confounding given extensive reviews on Mapania species being shade loving plants that grow well in conditions of damp and wet soils (Simpson, 1992;Shabdin et al, 2013aShabdin et al, , 2013bMiraadila et al, 2016a) and failing attempts to plant the species in new locations (Z. Shabdin, pers.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…During the course of 130 days post-transplanting, M. cuspidata developed an average of 7.7 new leaves with leaf production rate of 15.8 days/leaf. The findings of this study are substantial yet confounding given extensive reviews on Mapania species being shade loving plants that grow well in conditions of damp and wet soils (Simpson, 1992;Shabdin et al, 2013aShabdin et al, , 2013bMiraadila et al, 2016a) and failing attempts to plant the species in new locations (Z. Shabdin, pers.…”
Section: Discussionmentioning
confidence: 80%
“…The diversity of Mapania species from Sarawak is tremendous, with 31 out of 71 world's total number are recorded (Miraadila et al, 2016). Studies on Mapania of Sarawak since 2008 by Shabdin et al (2013aShabdin et al ( , 2013bShabdin et al ( , 2016 has observed the high tendency of endemicity of the species to Borneo (M. longiflora, M. angustifolia, M. lorea, M. debilis, M. maschalina, M. obscuriflora, M. richardsii, M. borneensis, M. latifolia and M. hispida), and hyper-endemicity (M. foxworthyi, M. graminea, M. sapuaniana and M. multiflora). Only a few species are widespread; for instance, M. cuspidata.…”
Section: Introductionmentioning
confidence: 99%
“…The studies of genus Mapania in Borneo and particularly Sarawak has been neglected since the last enumeration by Simpson (1992) until Shabdin et al (2013aShabdin et al ( & 2013b added two new species and another three recently, with one new record (Miraadila & Shabdin, 2016) to the list making it 31 species in total. In attaining the important knowledge of this valuable genus, a comprehensive research has been conducted to study the delimitation of the genus in Sarawak.…”
Section: Resultsmentioning
confidence: 99%
“…The number however has increased as several new species been discovered recently, particularly from Malesian region i.e. Shabdin et al (2013aShabdin et al ( & 2013b, and Miraadila and Shabdin (2016). Mapania section Pandanophyllum is endemic to Asia, Indomalesia, Australia and the Pacific Islands.…”
Section: Introductionmentioning
confidence: 99%